Calculated parenteral initial treatment of bacterial infections: Infections in the ear, nose, throat and mouth and jaw area - Olzowy, Bernhard (GMS Infect Dis, 2020)
This is the sixth chapter of the guideline “Calculated initial parenteral treatment of bacterial infections in adults – update 2018” in the 2(nd) updated version. The German guideline by the Paul-Ehrlich-Gesellschaft für Chemotherapie e.V. (PEG) has been translated to address an international audience. The chapter deals with the antibacterial treatment of more severe infections of the ear, the nose, the throat and the maxillofacial region, including odontogenic and salivary gland infections.